Observations from a Multicentre Study on the Use of the Sputum Specimen in Patients Hospitalized with Community-Acquired Pneumonia - EL Taylor; TJ Marrie; MJ Fine; DS Obroskyl; WN Kapoor; C Coley; DE Singer (Canadian Journal of Infectious Diseases)
OBJECTIVE: To describe the use of sputum Gram stain and culture in patients with community-acquired pneumonia (CAP) and to determine the factors that are associated with obtaining sputum for culture.